Electrolyte containing silane additive and lithium ion battery

By using silane-containing additives in the electrolyte of lithium-ion batteries, the problem of interface damage caused by volume expansion of silicon-based negative electrode materials is solved, and the circulation and rate performance of lithium batteries are significantly improved.

CN119725753APending Publication Date: 2025-03-28EVE ENERGY CO LTD

Patent Information

Application Number
CN202411920071.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The silicon-based anode material causes interface damage due to volume expansion in lithium-ion batteries, which in turn affects the cycle stability and rate performance of the battery.

Method used

The electrolyte containing silane additives is introduced into the electrolyte, and the reaction with the H2O or HF in the electrolyte is carried out through the Si-N bond and Si-O-Si bond, which removes water and suppresses acid, and improves the stability of the electrolyte; at the same time, the F element forms a high ionic conductivity LiF at the interface of the negative electrode, increases the unsaturated bonds on the surface of the positive and negative electrode to form a polymer film, and improves the stability of the SEI and CEI films.

Benefits of technology

Significantly improve the circulation and rate performance of lithium batteries, alleviate the expansion of silicon negative electrodes, and extend the service life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119725753A_ABST
    Figure CN119725753A_ABST
Patent Text Reader

Abstract

The invention specifically discloses an electrolyte containing a silane additive and a lithium ion battery. The electrolyte containing the silane additives comprises a first additive and a second additive, the first additive comprises organic fluoride, and the organic fluoride comprises N, O-bis (trimethylsilyl) trifluoroacetamide, N-methyl-N-(trimethyl-d9-silyl) trifluoroacetamide, 2, 2, 2-trifluoro-N, N-bis (trimethylsilyl) trifluoroacetamide, N, N-bis (trimethylsilyl) trifluoroacetamide, N, N-bis (trimethylsilyl) trifluoroacetamide, N, N-bis (trimethylsilyl) trifluoroacetamide, N, N-bis (trimethylsilyl) trifluoroacetamide, N, N-bis ( the solvent is at least one of N, N-di (trimethylsilyl) acetamide and N-tert-butyl dimethyl silyl-N-methyl trifluoroacetamide; the chemical structure of the second additive is shown as a formula I: # imgabs0 #, at least one of R1, R2, R3 and R4 is a silicon-oxygen-containing group, and a Si-O-Si bond is formed by a center Si connected with R1, R2, R3 and R4 and at least one of R1, R2, R3 and R4. The method has the advantage of improving the cycle performance and the rate capability of the lithium battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of lithium batteries, and in particular to an electrolyte containing silane additives and a lithium ion battery. Background Art

[0002] With the rapid development of mobile devices, electric vehicles, home appliances, smart wearable devices, 3C products and other fields, lithium batteries, as a new type of secondary battery with high energy density, high cycle times and long service life, have been widely used in these fields. At the same time, with the rapid development of new energy vehicles and energy storage industries, lithium batteries have gradually become the main power source in these fields.

[0003] The main components of lithium-ion batteries include positive electrode sheets, negative electrode sheets, separators and electrolytes. Among them, the electrolyte is an important component of lithium-ion batteries. During the first charge and discharge process of lithium-ion batteries, the electrolyte reacts with the negative electrode material at the solid-liquid interface to form a passivation layer SEI film at the interface of the negative electrode material. Lithium ions can be freely embedded and removed through the SEI film to achieve battery charging and discharging. Therefore, the SEI film has an important influence on the irreversible capacity, cycle performance, lithium insertion stability and kinetic properties of lithium-ion batteries.

[0004] Silicon materials have great potential in lithium-ion battery negative electrode materials due to their ultra-high theoretical specific capacity (3579mAh / g), suitable operating voltage, abundant reserves and good safety. However, compared with graphite, the volume change of silicon negative electrode during charging and discharging is as high as 300%. The large volume change can easily cause problems such as electrode particle pulverization and active material shedding. It will also destroy the SEI film on the surface of the negative electrode, causing the continuous growth of the SEI film and continuous consumption of active lithium, deteriorating the cycle life of the negative electrode material, and further deteriorating the cycle stability of the lithium-ion battery. Due to the volume effect of silicon-based negative electrode materials, it is difficult for silicon-based negative electrodes to form a stable solid electrolyte interface film in the electrolyte, and the electrode structure is destroyed during the battery cycle. The exposed silicon-based surface will continuously form a new solid electrolyte interface film, resulting in corrosion of the negative electrode material and capacity decay.

[0005] In order to solve the problems of volume expansion of silicon-based negative electrodes and the resulting interface damage, introducing electrolyte additives into the electrolyte to promote the formation of SEI film and thus prevent electrolyte decomposition is a simple and cost-effective method. Summary of the invention

[0006] In order to solve the problems in the prior art, the present application provides an electrolyte and a lithium ion battery containing a silane additive.

[0007] In a first aspect, the present application provides an electrolyte containing a silane additive, which adopts the following technical solution:

[0008] An electrolyte containing a silane additive, comprising a first additive and a second additive, wherein the first additive comprises an organic fluoride, and the organic fluoride comprises at least one of N,O-bis(trimethylsilyl)trifluoroacetamide, N-methyl-N-(trimethyl-d9-silyl)trifluoroacetamide, 2,2,2-trifluoro-N,N-bis(trimethylsilyl)acetamide, and N-tert-butyldimethylsilyl-N-methyltrifluoroacetamide;

[0009] The chemical structure of the second additive is shown in Formula I:

[0010]

[0011] Among them, at least one of R1, R2, R3, and R4 is a silicon-oxygen group, and the central Si connected to R1, R2, R3, and R4 forms a Si-O-Si bond with at least one of R1, R2, R3, and R4.

[0012] In this application, by using the first additive and the second additive in combination, the Si-N bond and Si-O-Si bond contained in the additive system can react with H20 or HF in the electrolyte to remove water and inhibit acid, thereby improving the stability of the electrolyte and helping to improve the cycle stability of the lithium-ion battery; in addition, the F element in the first additive can form LiF with high ionic conductivity at the negative electrode interface, thereby improving the rate performance of the lithium battery; further, the large number of unsaturated bonds contained in the second additive can form a polymer film at the positive and negative electrode surfaces, thereby significantly improving the stability of the CEI film and SEI film on the positive and negative electrode surfaces, and the above-mentioned polymer film can not only inhibit the dissolution of transition metal ions at the positive electrode, but also buffer the volume expansion generated by the silicon negative electrode, thereby improving the cycle performance of the lithium battery. Therefore, the combination of the first additive and the second additive can play a coordinated role and significantly improve the cycle performance and rate performance of the lithium battery.

[0013] Preferably, in the second additive, R1, R2, R3, and R4 are selected from at least one of -CH3, -CHCH2, -OSiCH3CH3CHCH2, and -OSiCH3CH3CH3, and at least one of R1, R2, R3, and R4 is selected from -OSiCH3CH3CHCH2.

[0014] By further optimizing R1, R2, R3, and R4 to meet the above conditions, it is possible to ensure that the second additive has good solubility in the electrolyte while reducing the film-forming impedance of the second additive at the positive and negative electrodes. It is also beneficial to take into account the long-term coordination of the second additive and the first additive, so that the first additive and the second additive cooperate to improve the overall role of the electrolyte in the battery, which helps to further optimize the cycle performance and rate performance of the lithium battery.

[0015] Preferably, the first additive includes N,O-bis(trimethylsilyl)trifluoroacetamide, and the second additive includes tetrakis(dimethylvinylsiloxy)silane.

[0016] When the first additive and the second additive are the above two substances, the combination of the two has the best effect, and the electrolyte prepared by the two and other electrolyte components has better performance, which is more conducive to the overall performance optimization of the battery. Among them, the structural formula of N,O-bis(trimethylsilyl)trifluoroacetamide is The CAS number is 25561-30-2; the structural formula of tetrakis(dimethylvinylsiloxy)silane is The CAS number is 60111-54-8.

[0017] Preferably, the mass proportion of the first additive in the electrolyte is 0.5%-3%; the mass proportion of the second additive in the electrolyte is 0.1%-1%.

[0018] By controlling the mass ratio of the first solvent and the second solvent in the electrolyte, not only can the number of Si-N bonds and Si-O-Si bonds in the electrolyte be adjusted to remain within a reasonable range, the water inhibition and acid removal effect in the electrolyte can be exerted for a long time, and the stability of the electrolyte can be improved, but also the unsaturated bonds can be promoted to promote the film formation on the surface of the positive and negative electrodes.

[0019] Preferably, it also includes an organic solvent and a lithium salt.

[0020] Preferably, the concentration of the lithium salt in the electrolyte is 1-1.5 mol / L.

[0021] Preferably, the lithium salt comprises lithium hexafluorophosphate.

[0022] Preferably, the organic solvent comprises at least one of a linear carbonate, a cyclic carbonate and a carboxylate;

[0023] Preferably, the linear carbonate includes at least one of dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate and methyl propyl carbonate; the cyclic carbonate includes at least one of ethylene carbonate, fluoroethylene carbonate and propylene carbonate; the carboxylic acid ester includes at least one of methyl formate, ethyl acetate, methyl propionate, propyl acetate and propyl propionate.

[0024] In the present application, by using the above-mentioned organic solvent, on the one hand, the carboxylic acid ester in the organic solvent system can reduce the influence of the high film-forming impedance of the second additive on the film-forming on the surface of the positive and negative electrodes, improve the stability of the SEI film generated on the surface of the positive and negative electrodes, alleviate the expansion of the silicon negative electrode, and help improve the cycle performance of the lithium battery; on the other hand, the above-mentioned organic solvent system can adjust the viscosity of the electrolyte to maintain it within a reasonable range, which helps to ensure that the electrolyte always has high ion transport characteristics during the cycle of the lithium battery, and helps to improve the rate performance of the lithium battery.

[0025] Preferably, the mass ratio of the linear carbonate, the cyclic carbonate and the carboxylic acid ester is 30-70:20-40:10-30.

[0026] By adjusting the mass proportion of carboxylic acid ester in the organic solvent, the viscosity of the electrolyte can be reduced while ensuring the stability of film formation at the negative electrode and maintaining the electrolyte with strong ion conductivity.

[0027] In a second aspect, the present application provides a lithium-ion battery, which adopts the following technical solution:

[0028] A lithium ion battery comprises a positive electrode sheet, a separator, a negative electrode sheet and the electrolyte as described above. DETAILED DESCRIPTION

[0029] For better understanding and implementation, the technical solution of the present application will be clearly and completely described below in conjunction with embodiments. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all of the embodiments.

[0030] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which this application belongs. The terms used herein in the specification of this application are only for the purpose of describing specific embodiments and are not intended to limit this application.

[0031] Unless otherwise indicated, all numerical values ​​expressing quantities of ingredients, reaction conditions, and so forth used in the specification and claims are to be understood as modified by the term “about.” Accordingly, unless indicated to the contrary, the numerical parameters set forth herein are approximations that can vary depending upon the desired properties desired to be obtained.

[0032] As used herein, "and / or" means one or all of the mentioned elements.

[0033] As used herein, “including” and “comprising” encompasses the case where only the stated elements are present as well as the case where there are other elements other than the stated elements.

[0034] All percentages in this application are by weight unless otherwise stated.

[0035] Unless otherwise indicated, "a", "an", "an" and "the" used in this specification are intended to include "at least one" or "one or more". For example, "a component" means one or more components, so more than one component may be considered and may be employed or used in the implementation of the embodiment.

[0036] Example 1

[0037] 1. Preparation of Electrolyte

[0038] The mass proportion of the first additive in the electrolyte is 2%, the mass proportion of the second additive is 0.5%, the mass proportion of linear carbonate, cyclic carbonate and carboxylic acid ester in the organic solvent is 50:35:15, and the lithium salt concentration is 1.2 mol / L.

[0039] The first additive is N-methyl-N-(trimethyl-d9-silyl) trifluoroacetamide, CAS No. 945623-67-6, and the second additive is tetrakis(dimethylvinylsiloxy)silane, the structural formula of which is The CAS number is 60111-54-8;

[0040] The lithium salt is lithium hexafluorophosphate;

[0041] The linear carbonates are diethyl carbonate DEC and ethyl methyl carbonate EMC, the cyclic carbonates are fluoroethylene carbonate FEC and ethylene carbonate EC, and the carboxylic acid ester is propyl acetate EP (DEC:EMC:FEC:EC:EP=20:30:10:25:15);

[0042] The linear carbonate, cyclic carbonate and carboxylate are stirred and mixed evenly to obtain a first mixture; the lithium salt is added to the first mixture and stirred and mixed evenly to obtain a second mixture; the first additive and the second additive are added to the second mixture and stirred and mixed evenly to obtain an electrolyte.

[0043] 2. Preparation of positive electrode

[0044] The ternary material NCM (LiNi 0.9 Co 0.05 Mn 0.05 O2) positive electrode active material, binder PVDF (polyvinylidene fluoride), conductive agent SP (conductive carbon black Super-P) are mixed and stirred evenly in a mass ratio of 96:1.8:2.2 to obtain positive electrode slurry, and then the positive electrode slurry is coated on aluminum foil through a coating process, and the positive electrode sheet is obtained after drying and cold pressing processes.

[0045] 3. Preparation of negative electrode sheet

[0046] Silicon-carbon negative electrode material, conductive agent SP (conductive carbon black Super-P), SWCNT (single-walled carbon nanotube) and binder PAA (polyacrylic acid) are mixed and stirred in a mass ratio of 83.5:8:0.5:8 to obtain negative electrode slurry, and the solid content is controlled at 30%. The negative electrode slurry is then coated on the current collector on the copper foil through a coating process, and the negative electrode sheet is obtained after vacuum drying and cold pressing processes.

[0047] 4. Selection of isolation film

[0048] Polyethylene (PE) + ceramics are selected as the isolation membrane for lithium-ion batteries.

[0049] 5. Preparation of Lithium-ion Batteries

[0050] The positive electrode sheet, the isolation film, and the negative electrode sheet are stacked in order, so that the isolation film is placed between the positive electrode sheet and the negative electrode sheet to play an isolating role, and then a bare battery cell is obtained; the bare battery cell is placed in an outer packaging shell, and after drying, an electrolyte is injected, and after vacuum packaging, standing, forming, shaping and other processes, a soft-pack lithium-ion battery is obtained.

[0051] Example 2

[0052] 1. Preparation of Electrolyte

[0053] The mass proportion of the first additive in the electrolyte is 0.5%, the mass proportion of the second additive is 0.1%, the mass proportion of linear carbonate, cyclic carbonate and carboxylic acid ester in the organic solvent is 70:20:10, and the lithium salt concentration is 1 mol / L.

[0054] The first additive is 2,2,2-trifluoro-N,N-bis(trimethylsilyl)acetamide, CAS No. 21149-38-2, and the structural formula of the second additive is The CAS number is 60111-52-6;

[0055] The lithium salt is lithium hexafluorophosphate;

[0056] The linear carbonates are dimethyl carbonate DMC and ethyl methyl carbonate EMC, the cyclic carbonates are fluoroethylene carbonate FEC and propylene carbonate PC, and the carboxylic acid ester is propyl acetate EP (DMC:EMC:FEC:PC:EP=30:40:10:10:10;

[0057] The linear carbonate, cyclic carbonate and carboxylate are stirred and mixed evenly to obtain a first mixture; the lithium salt is added to the first mixture and stirred and mixed evenly to obtain a second mixture; the first additive and the second additive are added to the second mixture and stirred and mixed evenly to obtain an electrolyte.

[0058] 2. Preparation of positive electrode

[0059] The ternary material NCM (LiNi 0.9 Co 0.05 Mn 0.05 O2) positive electrode active material, binder PVDF (polyvinylidene fluoride), conductive agent SP (conductive carbon black Super-P) are mixed and stirred evenly in a mass ratio of 96:1.8:2.2 to obtain positive electrode slurry, and then the positive electrode slurry is coated on aluminum foil through a coating process, and the positive electrode sheet is obtained after drying and cold pressing processes.

[0060] 3. Preparation of negative electrode sheet

[0061] Silicon-carbon negative electrode material, conductive agent SP (conductive carbon black Super-P), SWCNT (single-walled carbon nanotube) and binder PAA (polyacrylic acid) are mixed and stirred in a mass ratio of 83.5:8:0.5:8 to obtain negative electrode slurry, and the solid content is controlled at 30%. The negative electrode slurry is then coated on the current collector on the copper foil through a coating process, and the negative electrode sheet is obtained after vacuum drying and cold pressing processes.

[0062] 4. Selection of isolation film

[0063] Polyethylene (PE) + ceramics are selected as the isolation membrane for lithium-ion batteries.

[0064] 5. Preparation of Lithium-ion Batteries

[0065] The positive electrode sheet, the isolation film, and the negative electrode sheet are stacked in order, so that the isolation film is placed between the positive electrode sheet and the negative electrode sheet to play an isolating role, and then a bare battery cell is obtained; the bare battery cell is placed in an outer packaging shell, and after drying, an electrolyte is injected, and after vacuum packaging, standing, forming, shaping and other processes, a soft-pack lithium-ion battery is obtained.

[0066] Example 3

[0067] 1. Preparation of Electrolyte

[0068] The mass proportion of the first additive in the electrolyte is 3%, the mass proportion of the second additive is 1%, the mass proportion of linear carbonate, cyclic carbonate and carboxylic acid ester in the organic solvent is 30:40:30, and the lithium salt concentration is 1.5 mol / L.

[0069] The first additive is N-tert-butyldimethylsilyl-N-methyltrifluoroacetamide, CAS No. 77377-52-7, and the structural formula of the second additive is CAS number is 1529-65-3;

[0070] The lithium salt is lithium hexafluorophosphate;

[0071] The linear carbonates were methyl propyl carbonate MPC and ethyl methyl carbonate EMC, the cyclic carbonates were fluoroethylene carbonate FEC and ethylene carbonate EC, and the carboxylic acid ester was ethyl acetate EA (MPC:EMC:FEC:EC:EA=10:20:25:15:30;

[0072] The linear carbonate, cyclic carbonate and carboxylate are stirred and mixed evenly to obtain a first mixture; the lithium salt is added to the first mixture and stirred and mixed evenly to obtain a second mixture; the first additive and the second additive are added to the second mixture and stirred and mixed evenly to obtain an electrolyte.

[0073] 2. Preparation of positive electrode

[0074] The ternary material NCM (LiNi 0.9 Co 0.05 Mn 0.05 O2) positive electrode active material, binder PVDF (polyvinylidene fluoride), conductive agent SP (conductive carbon black Super-P) are mixed and stirred evenly in a mass ratio of 96:1.8:2.2 to obtain positive electrode slurry, and then the positive electrode slurry is coated on aluminum foil through a coating process, and the positive electrode sheet is obtained after drying and cold pressing processes.

[0075] 3. Preparation of negative electrode sheet

[0076] Silicon-carbon negative electrode material, conductive agent SP (conductive carbon black Super-P), SWCNT (single-walled carbon nanotube) and binder PAA (polyacrylic acid) are mixed and stirred in a mass ratio of 83.5:8:0.5:8 to obtain negative electrode slurry, and the solid content is controlled at 30%. The negative electrode slurry is then coated on the current collector on the copper foil through a coating process, and the negative electrode sheet is obtained after vacuum drying and cold pressing processes.

[0077] 4. Selection of isolation film

[0078] Polyethylene (PE) + ceramics are selected as the isolation membrane for lithium-ion batteries.

[0079] 5. Preparation of Lithium-ion Batteries

[0080] The positive electrode sheet, the isolation film, and the negative electrode sheet are stacked in order, so that the isolation film is placed between the positive electrode sheet and the negative electrode sheet to play an isolating role, and then a bare battery cell is obtained; the bare battery cell is placed in an outer packaging shell, and after drying, an electrolyte is injected, and after vacuum packaging, standing, forming, shaping and other processes, a soft-pack lithium-ion battery is obtained.

[0081] Example 4

[0082] 1. Preparation of Electrolyte

[0083] The mass proportion of the first additive in the electrolyte is 2%, the mass proportion of the second additive is 0.5%, the mass proportion of linear carbonate, cyclic carbonate and carboxylic acid ester in the organic solvent is 50:35:15, and the lithium salt concentration is 1.2 mol / L.

[0084] The first additive is N,O-bis(trimethylsilyl)trifluoroacetamide, CAS No. 25561-30-2, and the second additive is tetrakis(dimethylvinylsiloxy)silane, the structural formula of which is The CAS number is 60111-54-8;

[0085] The lithium salt is lithium hexafluorophosphate;

[0086] The linear carbonates are diethyl carbonate DEC and ethyl methyl carbonate EMC, the cyclic carbonates are fluoroethylene carbonate FEC and ethylene carbonate EC, and the carboxylic acid ester is EP propyl acetate (DEC:EMC:FEC:EC:EP=20:30:10:25:15;

[0087] The linear carbonate, cyclic carbonate and carboxylate are stirred and mixed evenly to obtain a first mixture; the lithium salt is added to the first mixture and stirred and mixed evenly to obtain a second mixture; the first additive and the second additive are added to the second mixture and stirred and mixed evenly to obtain an electrolyte.

[0088] 2. Preparation of positive electrode

[0089] The ternary material NCM (LiNi 0.9 Co 0.05 Mn 0.05 O2) positive electrode active material, binder PVDF (polyvinylidene fluoride), conductive agent SP (conductive carbon black Super-P) are mixed and stirred evenly in a mass ratio of 96:1.8:2.2 to obtain positive electrode slurry, and then the positive electrode slurry is coated on aluminum foil through a coating process, and the positive electrode sheet is obtained after drying and cold pressing processes.

[0090] 3. Preparation of negative electrode sheet

[0091] Silicon-carbon negative electrode material, conductive agent SP (conductive carbon black Super-P), SWCNT (single-walled carbon nanotube) and binder PAA (polyacrylic acid) are mixed and stirred in a mass ratio of 83.5:8:0.5:8 to obtain negative electrode slurry, and the solid content is controlled at 30%. The negative electrode slurry is then coated on the current collector on the copper foil through a coating process, and the negative electrode sheet is obtained after vacuum drying and cold pressing processes.

[0092] 4. Selection of isolation film

[0093] Polyethylene (PE) + ceramics are selected as the isolation membrane for lithium-ion batteries.

[0094] 5. Preparation of Lithium-ion Batteries

[0095] The positive electrode sheet, the isolation film, and the negative electrode sheet are stacked in order, so that the isolation film is placed between the positive electrode sheet and the negative electrode sheet to play an isolating role, and then a bare battery cell is obtained; the bare battery cell is placed in an outer packaging shell, and after drying, an electrolyte is injected, and after vacuum packaging, standing, forming, shaping and other processes, a soft-pack lithium-ion battery is obtained.

[0096] Example 5

[0097] The difference between this embodiment and embodiment 1 is that the mass proportion of the first additive in the electrolyte is 0.1%, and the mass proportion of the second additive in the electrolyte is 2%; other steps and parameter settings are consistent with embodiment 1.

[0098] Example 6

[0099] The difference between this embodiment and embodiment 1 is that the mass proportion of the first additive in the electrolyte is 3.5%, and the mass proportion of the second additive in the electrolyte is 0.02%; other steps and parameter settings are consistent with those in embodiment 1.

[0100] Example 7

[0101] The difference between this embodiment and embodiment 1 is that the electrolyte does not contain carboxylic acid ester. Specifically, an equal weight of cyclic carbonate is used to replace the carboxylic acid ester in embodiment 1. Other steps and parameter settings are consistent with embodiment 1.

[0102] Example 8

[0103] The difference between this embodiment and embodiment 1 is that the mass ratio of linear carbonate, cyclic carbonate and carboxylic acid ester in the organic solvent is 50:48:2. Specifically, the linear carbonate is diethyl carbonate DEC and ethyl methyl carbonate EMC, the cyclic carbonate is fluoroethylene carbonate FEC and vinyl carbonate EC, and the carboxylic acid ester is propyl acetate EP (DEC:EMC:FEC:EC:EP=20:30:10:38:2); other steps and parameter settings are consistent with those in embodiment 1.

[0104] Comparative Example 1

[0105] The difference between this comparative example and Example 1 is that the first additive and the second additive are not used in the electrolyte; other steps and parameter settings are consistent with Example 1.

[0106] Comparative Example 2

[0107] The difference between this comparative example and Example 1 is that the first additive is not used in the electrolyte; other steps and parameter settings are consistent with Example 1.

[0108] Comparative Example 3

[0109] The difference between this comparative example and Example 1 is that the second additive is not used in the electrolyte; other steps and parameter settings are consistent with Example 1.

[0110] Comparative Example 4

[0111] The difference between this comparative example and Example 1 is that the structural formula of the second additive is The CAS number is 15332-99-7, and other steps and parameter settings are consistent with those in Example 1.

[0112] Comparative Example 5

[0113] The difference between this comparative example and Example 1 is that the structural formula of the second additive is The CAS number is 3555-47-3, and other steps and parameter settings are consistent with those in Example 1.

[0114] Test Method

[0115] 1. The first coulombic efficiency test of lithium battery

[0116] The lithium batteries in the above embodiments and comparative examples were subjected to the first coulombic efficiency test. The specific test steps were as follows: at 25°C, the lithium ion battery was charged to 4.2V at a constant current and constant voltage rate of 0.33C, and allowed to stand for 10 minutes. Then, the lithium ion battery was discharged to 2.5V at a constant current rate of 0.33C, and allowed to stand for 10 minutes. The first coulombic efficiency of the lithium ion battery was calculated.

[0117] First coulombic efficiency (%) = total capacity of the lithium-ion battery discharged at 0.33C for the first time / total capacity of the lithium-ion battery charged at 0.33C for the first time × 100%.

[0118] 2. Lithium battery cycle performance test

[0119] 2.1. Lithium battery capacity retention rate during normal temperature cycling

[0120] The lithium batteries in the above embodiments and comparative examples were tested for capacity retention rate under normal temperature cycles. The specific test steps were as follows: at 25°C, the lithium ion battery was charged to 4.2V at a constant current and constant voltage rate of 1C, with a cut-off current of 0.05C, and allowed to stand for 10 minutes. Then, the lithium ion battery was discharged to 2.5V at a constant current rate of 1C, and allowed to stand for 10 minutes. This was considered one charge and discharge cycle. The lithium ion battery was charged and discharged for 1000 cycles according to the above method, and the capacity retention rate of the lithium ion battery after 1000 cycles of charge and discharge at 1C / 1C was calculated.

[0121] 2.2. Lithium battery high temperature cycle capacity retention rate

[0122] The lithium batteries in the above embodiments and comparative examples were tested for capacity retention rate under normal temperature cycles. The specific test steps were as follows: at 45°C, the lithium ion battery was charged to 4.2V at a constant current and constant voltage rate of 1C, with a cut-off current of 0.05C, and allowed to stand for 10 minutes. Then, the lithium ion battery was discharged to 2.5V at a constant current rate of 1C, and allowed to stand for 10 minutes. This was considered one charge and discharge cycle. The lithium ion battery was charged and discharged for 1000 cycles according to the above method, and the capacity retention rate of the lithium ion battery after 1000 cycles of charge and discharge at 1C / 1C was calculated.

[0123] The capacity retention rate (%) of a lithium-ion battery after N cycles = (discharge capacity at the Nth cycle / initial discharge capacity) × 100%, where N is the number of cycles of the lithium-ion battery.

[0124] 3. Rate performance test

[0125] The lithium batteries of the above embodiments and comparative examples were subjected to rate performance tests, and the specific test steps were as follows: at 25°C, the lithium ion battery was discharged at a constant current rate of 1C to 2.5V, and allowed to stand for 10 minutes, and then the lithium ion battery was charged at a constant current and constant voltage rate of 6C to 4.2V, with a cut-off current of 0.05C, and allowed to stand for 10 minutes, and the constant current charging capacity Q1 and the constant current and constant voltage charging total capacity Q2 of the lithium ion battery were recorded, and the 6C rate charging constant current charging ratio was calculated according to the following formula: 6C rate charging constant current charging ratio = constant current charging capacity Q1 / constant current and constant voltage charging total capacity Q2 × 100%.

[0126] Table 1

[0127]

[0128] In combination with Examples 1-4, Comparative Examples 1-5 and Table 1, it can be seen that the present application selects the first additive and the second additive for use in combination, and the Si-N bond and the Si-O-Si bond in the additive system can improve the stability of the electrolyte, and the fluorine element in the additive and the unsaturated bond can further improve the film formation stability of the positive and negative electrodes in the electrolyte, significantly alleviate the expansion of the silicon negative electrode, thereby significantly improving the cycle performance and rate performance of the lithium battery; and when the first additive is N, O-bis (trimethylsilyl) trifluoroacetamide and the second additive is tetrakis (dimethylvinylsiloxy) silane, the first additive and the second additive have the best combination effect, and the lithium battery cycle performance and rate performance are optimal.

[0129] In combination with Example 1, Examples 5-6 and Table 1, it can be seen that when the proportion of the first additive to the second additive is too high or too low, the number of Si-N bonds and Si-O-Si bonds in the electrolyte cannot be maintained within a reasonable range, which is not conducive to the cooperation of the two to exert the water inhibition and acid removal effect on the electrolyte, reduces the stability of the electrolyte, and is not conducive to the unsaturated bonds to promote the film formation on the positive and negative electrode surfaces, thereby reducing the cycle performance and rate performance of the lithium battery.

[0130] In combination with Example 1, Examples 7-8 and Table 1, it can be seen that when the organic solvent of the electrolyte does not contain carboxylic acid esters or the mass ratio of linear carbonates, cyclic carbonates and carboxylic acid esters in the organic solvent changes, the second additive will have a negative impact on the film-forming effect on the surface of the positive and negative electrodes, not only increasing the impedance of the surface film, but also reducing the film-forming stability of the surface film, which is not conducive to alleviating the expansion of the silicon negative electrode during the later cycle of the lithium battery; in addition, the viscosity of the electrolyte changes at this time, which is not conducive to the electrolyte maintaining a high ion transport characteristic, which will lead to a decrease in the cycle performance and rate performance of the lithium battery.

[0131] The above embodiments are only used to illustrate the technical solution of the present application rather than to limit the protection scope of the present application. Although the present application is described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that the technical solution of the present application can be modified or equivalently replaced, but these modifications or replacements are all within the protection scope of the present application.

Claims

1. An electrolyte containing a silane additive, characterized in that: The method comprises a first additive and a second additive, wherein the first additive comprises an organic fluoride, and the organic fluoride comprises at least one of N,O-bis(trimethylsilyl)trifluoroacetamide, N-methyl-N-(trimethyl-d9-silyl)trifluoroacetamide, 2,2,2-trifluoro-N,N-bis(trimethylsilyl)acetamide, and N-tert-butyldimethylsilyl-N-methyltrifluoroacetamide; The chemical structure of the second additive is shown in Formula I: Among them, at least one of R1, R2, R3, and R4 is a silicon-oxygen group, and the central Si connected to R1, R2, R3, and R4 forms a Si-O-Si bond with at least one of R1, R2, R3, and R4.

2. The electrolyte containing silane additives according to claim 1, characterized in that: In the second additive, R1, R2, R3, and R4 are selected from at least one of -CH3, -CHCH2, -OSiCH3CH3CHCH2, and -OSiCH3CH3CH3, and at least one of R1, R2, R3, and R4 is selected from -OSiCH3CH3CHCH2.

3. The electrolyte containing silane additives according to claim 1, characterized in that: The first additive includes N,O-bis(trimethylsilyl)trifluoroacetamide, and the second additive includes tetrakis(dimethylvinylsiloxy)silane.

4. The electrolyte containing silane additives according to claim 1, characterized in that: The mass proportion of the first additive in the electrolyte is 0.5%-3%; the mass proportion of the second additive in the electrolyte is 0.1%-1%.

5. The electrolyte containing silane additives according to any one of claims 1 to 4, characterized in that: It also includes organic solvents and lithium salts.

6. The electrolyte containing silane additives according to claim 5, characterized in that: The concentration of the lithium salt in the electrolyte is 1-1.5 mol / L.

7. The electrolyte containing silane additives according to claim 5, characterized in that: The organic solvent includes at least one of linear carbonate, cyclic carbonate and carboxylic acid ester.

8. The electrolyte containing silane additives according to claim 7, characterized in that: The linear carbonate includes at least one of dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate and methyl propyl carbonate; the cyclic carbonate includes at least one of ethylene carbonate, fluoroethylene carbonate and propylene carbonate; the carboxylic acid ester includes at least one of methyl formate, ethyl acetate, methyl propionate, propyl acetate and propyl propionate.

9. The electrolyte containing silane additives according to claim 7, characterized in that: The mass ratio of the linear carbonate, the cyclic carbonate and the carboxylic acid ester is 30-70:20-40:10-30.

10. A lithium ion battery, characterized in that: The invention comprises a positive electrode sheet, a separator, a negative electrode sheet and an electrolyte as claimed in any one of claims 1 to 9.

Citation Information

Patent Citations

  • Composition for addition to electrolyte solutions containing silyl group-containing compound, electrolyte solution for nonaqueous electricity storage devices containing said composition, and lithium ion secondary battery containing said electrolyte solution

    CN105745779A

  • Electrolyte and secondary battery using same

    CN113130990A

  • Nonaqueous electrolyte solution and nonaqueous electrolyte battery

    CN114207901A

  • Electrolyte Formulations for Optimal Performance in Si-Containing Lithium Ion Batteries

    US20240079653A1

Cited By

  • Application of electrolyte additive, electrolyte and lithium ion battery

    CN122246271A